PERBANDINGAN UJI Treponema pallidum Haemagglutination Assay (TPHA) DAN IMUNOKROMATOGRAFI SEBAGAI DETEKSI SIFILIS di PUSKESMAS MEDAENG: COMPARISON OF Treponema pallidum Haemagglutination Assay (TPHA) TEST AND IMMUNOCHROMATOGRAPHY AS SYPHILIS DETECTION AT MEDAENG PUBLIC HEALTH CENTER - Romadhon, Desi Fitriatur; Wijayanti, Christina Destri Wiwis; Sundari, Titik; Harmoko, Deni (Jurnal SainHealth, 2024)
Syphilis is a sexually transmitted infection caused by the bacteria Treponema pallidum. Syphilis detection can be done using the Treponema pallidum Haemagglutination Assay (TPHA) method and immunochromatography. Treponema pallidum Haemaglutination Assay (TPHA) is a specific antibody test to detect Treponema pallidum but the process is long and expensive, compared to fast and relatively cheap immunochromatography. This study aimed to compare the Treponema pallidum Haemagglutination Assay (TPHA) method and immunochromatography as syphilis detection by looking at their positive and negative reaction percentage. The type of research used was descriptive-analytical observation. The results of the Treponema pallidum Haemagglutination Assay (TPHA) examination were positive for 10 samples (50%) and negative for 10 samples (50%). Meanwhile, positive immunochromatography was in 8 samples (40%) and negative for 12 samples (60%). It can be concluded that TPHA and immunochromatography have a different result. Keywords: syphilis, immunochromatography, TPHA, sensitivity, specificity